2010
DOI: 10.1111/j.1463-6395.2010.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of type II collagen in the lingual mucosa of rats during the morphogenesis of circumvallate papillae

Abstract: Iwasaki, S., Aoyagi, H. and Yoshizawa, H. 2011. Localization of type II collagen in the lingual mucosa of rats during the morphogenesis of circumvallate papillae.-Acta Zoologica (Stockholm) 92: 67-74.Immunoreactivity specific for type II collagen was recognized first in the mesenchymal connective tissue just beneath the circumvallate papilla placode in fetuses on E13. At this stage, most of the lingual epithelium was pseudostratified epithelium composed of one or two layers of cuboidal cells. However, the epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…To demonstrate the effectiveness of our method, in the present study we examined the immunofluorescence of immuno-stained keratins and collagens and the images obtained, in transmission mode, of the lingual mucosa of the filiform and circumvallate papillary areas of tongues of fetus and juvenile rats by LSM. By combining images, we were able to define clearly the histological locations of keratin 13 (K13) and keratin 14 (K14) in the lingual epithelium (Iwasaki et al, 2006a(Iwasaki et al, , 2011a and those of collagen II (CII) and collagen III (CIII) in the lingual connective tissue , 2011b. Furthermore, we demonstrated that our newly developed technique for localization of pairs of antigens should be useful for investigations of very small specimens, such as fetal tissues and organs .…”
Section: Introductionmentioning
confidence: 92%
“…To demonstrate the effectiveness of our method, in the present study we examined the immunofluorescence of immuno-stained keratins and collagens and the images obtained, in transmission mode, of the lingual mucosa of the filiform and circumvallate papillary areas of tongues of fetus and juvenile rats by LSM. By combining images, we were able to define clearly the histological locations of keratin 13 (K13) and keratin 14 (K14) in the lingual epithelium (Iwasaki et al, 2006a(Iwasaki et al, , 2011a and those of collagen II (CII) and collagen III (CIII) in the lingual connective tissue , 2011b. Furthermore, we demonstrated that our newly developed technique for localization of pairs of antigens should be useful for investigations of very small specimens, such as fetal tissues and organs .…”
Section: Introductionmentioning
confidence: 92%